Synthesis of Chitosan and Ulva sp.-Based Hydrogel Beads as Bioadsorbents for Heavy Metal Removal of Pb and Cd - Dyah Safrina Hardiningtyas; Faza Maulida; Bustami Ibrahim (Journal of Marine and Coastal Science, 2026)
Water pollution remains a critical global concern, with heavy metals such as lead (Pb) and cadmium (Cd) posing serious health and environmental risks. Adsorption using biobased materials has emerged as a sustainable solution for mitigating heavy metal contamination in water. Among various bioadsorbents, chitosan and seaweed (Ulva sp.) are notable for their abundance, environmental friendliness, and effectiveness in removing toxic metals. While chitosan and Ulva have been studied individually for their adsorption properties, research on their combined use in hydrogel beads is limited, especially when their compositional ratios are systematically varied. The present study seeks to address this gap by evaluating how the incorporation and proportion of Ulva affect the structural, functional, and adsorptive properties of chitosan-based hydrogel beads, with a specific focus on the simultaneous removal of Pb and Cd from water. Hydrogel beads were synthesized with different chitosan-to-Ulva ratios (U1 [1:0], U2 [1:0.1], and U3 [1:0.5]) and characterized for swelling behavior, gel fraction, and heavy metal adsorption capacity. Results show that adding Ulva to the chitosan matrix significantly enhances the bioadsorbent’s performance, especially at the highest tested ratio (U3), which achieved an average bead diameter of 3.7 ± 0.01 mm, high swelling, and stable gel fraction. Most importantly, U3 beads demonstrated superior removal efficiencies for both Pb and Cd, highlighting the synergistic effect of combining chitosan and Ulva. These findings suggest that chitosan–Ulva hydrogel beads are promising, eco-friendly bioadsorbents for remediating heavy metal-contaminated water and could play an important role in sustainable water treatment technologies.